Three-Dimensional, Multiplanar, Ultrasound-Guided, Radial Nerve Block. Issue 6 (1st November 2007) - Foxall, Gillian L.; Hardman, Jonathan G.; Bedforth, Nigel M.
Abstract : Objective: We describe the use of 3-dimensional, multiplanar ultrasound imaging for peripheral nerve block. Case Report: To illustrate the potential usefulness of the technique, we present a case in which real-time 3-dimensional, multiplanar ultrasound was used to assist in the performance of a radial nerve block. Conclusions: Three-dimensional, multiplanar ultrasound in real-time has the potential to improve nerve identification and accuracy of needle placement in regional anesthesia.